Negotiation: Always There and Never Called by Its Name Results From the Literature and From Empirical Experiments - Soliman, Cherine (The Arab Journal of Administration, 2022)
As reflected by a growing body of literature, conflict and negotiation have always been at the heart of our environment. One should then assume that negotiation skills have become a fundamental life knowhow. Beyond the international crisis intensification, creating complexity in conflict situations, the literature also brings evidence that conflict is an embedded dimension of every individual life. Does that mean that citizens of the world today are all equipped with the right “ready-to-use” negotiation skills? In order to investigate this question, we developed an empirical study focused on a sample of Egyptian highly educated professionals working in multinationals. We worked with 180 professionals attending an MBA program, collected data over three years, using questionnaires and word analysis. Results revealed a severe lack in negotiation education yet also gave evidence for a strong authentic need/demand. Recommendations resulting from this paper highlight the importance of including education to negotiation in the curriculum at the school and university levels. Indeed, the literature shows that good negotiation skills in highly conflictual environments will lead to business success and happy citizenship.